Transport of Radioactive Particle in the Middle East Following a Hypothetical Nuclear Release - Khatib, Imad (J. of Applied Sciences in Environmental Sanitation, 2008)
The mathematical air transport and dispersion model MEMO is applied to study the atmospheric air masses flow in a geographic are of 500 x 500 sq.km (domain) on the Middle East region. The aim is to investigate the role of regional atmospheric air flow phenomena in the transport of radioactive particles. The results showed that mesoscale air flow phenomena are mostly dominant in the region under study. Hence, following a hypothetical release of nuclear radioactive particles from the Dimona nuclear facilities situated in the south of Israel, major communities in Israel, Palestinian Authority, Jordan, Lebanon and Syria may be exposed within the first forty eight hours after the nuclear release.
Keywords: Dimona Nuclear plant, mesoscale flow, MEMO, cross-boarder pollution transport